Impactos da reforma trabalhista sob a ótica do princípio constitucional do acesso acesso à justiça e justiça gratuita - Ribeiro, Bruna Maria modesto (2021)
This monograph aims to understand and analyze the impacts of Law 13,467/2017 in the context of the Labor Process after the modification of the criteria for granting the benefits of free justice and the rules regarding the payment of legal fees. The deductive method analyzes the concept of access to justice and free justice, especially from the perspective of the Labor Process. Therefore, it will be used the bibliographic revision, especially the works of Mauro Cappeletti and Bryant Garth and Kazuo Watanabe, which are fundamental for the study of the principle of access to justice. It also intends to discuss the specificities involving the gratuitousness of justice in labor legislation. After, analyze, individually, the arts. 790-B, caput and §4º; 791-A, § 4º; and 844, §2º, of the CLT, which deal with the changes implemented by Law 13,467/2017 regarding the criteria for granting the benefits of free justice and the succumbing of the individual beneficiary of it. Thus, an analysis of the Right Action of Unconstitutionality n. 5677 is made, discussing whether the implemented changes have support in the Federal Constitution. Therefore, the theoretical analysis, together with the examination of the current legislation, shows that the Labour Reform was responsible for substantially limiting access to Labour Justice, in so far as the new criteria for granting justice free of charge and the new rules in the event of the recipient’s succumbing impose disproportionate burdens on the unsuitable party, thus being able to speak, in the anomalous phenomenon of free justice onerous in the labor process.